The relationship between psychological and sociocultural adaptation and cultural intelligence within a sample of national collective sports teams players - AIMEUR, Mounira; BALAMANE, Ferhat (sports creativity, 2024)
This study aims to identify whether there is a relationship between psychological and sociocultural adaptation and cultural intelligence among a sample of national collective team sports players. Furthermore, the study seeks to reveal the level of these two variables among this sample, as well as the effect of certain other variables - age, gender - on the results of the players in response to the measures used in this study. This study was applied to a sample of twenty-nine players from different Algerian states, who play for national collective sports teams (volleyball, basketball, handball), both of the short scale of psychological and sociocultural adaptation and the short scale of cultural intelligence were used in the study. A set of statistical tests were used including Pearson's coefficient, statistical significance test (T) and statistical significance test (F) to analyze the study data.The study concluded that there is a correlation between psychological and sociocultural adaptation and cultural intelligence, and that the level of both variables is high in the sample studied, in addition to the fact that there is no statistically significant differences related to gender and age variables in response to study scals .